Prenatal care and obstetric outcome based on the insurance status of immigrants in South Korea: a retrospective cohort study - Yun Sung Jo; Ji Soo Um; Kyung Eun Lee; Sa Jin Kim; Jae Eun Shin (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: Immigrants face various problems in accessing healthcare because of lacking medical insurance. This study retrospectively evaluated the effect of insurance on the prenatal care and the obstetric outcomes of immigrants in South Korea. The main objective was to compare the obstetric complications between uninsured and insured immigrants, and the secondary objective was to compare the prenatal care and maternal nutrition during pregnancy. Methods: Using data from the hospital records, we compared the perinatal outcomes of insured and uninsured women who delivered at Buchoen St. Mary’s Hospital between 2010 and 2020, including the sociodemographic data, prenatal care, obstetric outcomes, and maternal nutrition. The association between insurance status and the various perinatal outcomes of immigrants was assessed using multivariate logistic regression, adjusting for potential confounding variables. Results: In total, 320 immigrant women were included, and 52 (16%) were uninsured. Uninsured immigrants had fewer numbers and a later initiation of prenatal care visits (7.75 ± 4.44 vs. 12.45 ± 3.75, p < 0.001; 1st trimester: 36.5% vs. 66.8%, p < 0.001, respectively), and a lower percentage of an adequate Kessner index score (26.9% vs. 63.8%; p < 0.001, respectively) than insured immigrants. The obstetric complications and maternal nutrition did not significantly vary. After adjusting for the confounding factors, the uninsured immigrants had a higher odds ratio of less-than-adequate prenatal care (adjusted odds ratio (OR) = 5.18; 95% confidence interval: 2.54–10.53; p < 0.001). Conclusions: Uninsured immigrants had inadequate prenatal care compared to insured immigrants, but this did not result in adverse obstetric and maternal outcomes.